2020
DOI: 10.1242/dev.186643
|View full text |Cite
|
Sign up to set email alerts
|

Role of nutrient-driven O-GlcNAc-post-translational modification in pancreatic exocrine and endocrine islet development

Abstract: Although the developing pancreas is exquisitely sensitive to nutrient supply in utero, it is not entirely clear how nutrient-driven posttranslational modification of proteins impacts the pancreas during development. We hypothesized that the nutrient-sensing enzyme O-GlcNAc transferase (Ogt), which catalyzes an O-GlcNAc-modification onto key target proteins, integrates nutrient-signaling networks to regulate cell survival and development. In this study, we investigated the heretofore unknown role of Ogt in exoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 53 publications
(76 reference statements)
6
39
0
Order By: Relevance
“…4 , H and I ). These data suggest that increased ER stress may contribute to cell death in αTC-1 cells when O-GlcNAcylation is blocked, consistent with the reported effects of OGT inhibition in other pancreatic cells ( 14 , 16 ) in vivo .
Figure 4 αOGT KO mice show significant reduction in α-cell mass at 6 months .
…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4 , H and I ). These data suggest that increased ER stress may contribute to cell death in αTC-1 cells when O-GlcNAcylation is blocked, consistent with the reported effects of OGT inhibition in other pancreatic cells ( 14 , 16 ) in vivo .
Figure 4 αOGT KO mice show significant reduction in α-cell mass at 6 months .
…”
Section: Resultssupporting
confidence: 88%
“…We reported that loss of O-GlcNAcylation in the β-cell leads to cell failure and diabetes in mice due to increased endoplasmic reticulum (ER) stress and apoptosis ( 14 ). Ablation of OGT in pancreatic progenitors also leads to an increased apoptosis ( 16 ). Independent of its role in cell survival, OGT also regulates insulin secretion at basal ( 14 ) and in obesity conditions in part through SERCA2 ( 17 ).…”
mentioning
confidence: 99%
“…In parallel, a high level of O‐GlcNAcylation occurs in the nuclei of β‐cells 18 , which is consistent with the high expression of Ogt in the pancreas (Figure 2) 19,20 . During islet development, Ogt – expressed in pancreatic epithelial progenitor cells – plays an important role in cell survival, and thus pancreatogenesis, which is mediated through pancreatic and duodenal homeobox 1 and p53 21 . In adult mice, greater O‐GlcNAcylation, induced by glutamine:fructose‐6‐aminotransferase overexpression, causes hyperinsulinemia 22 .…”
Section: Pancreatic β‐Cells: a Primary Target In Diabetes Mellitussupporting
confidence: 73%
“…A most recent study showed that Ogt null mutation in the pancreatic epithelium impacts the development of endocrine and exocrine pancreases. RNA-seq revealed that OGT targets, such as Pdx1, Ptf1a, and p53, are downregulated to induce apoptosis of pancreatic progenitors [138]. Besides, the translocation of β-cell-specific transcription factor NeuroD1 from the cytosol to the nucleus under high glucose conditions is catalyzed by OGN to induce insulin expression in MIN6 cells [139].…”
Section: O-glcnac Is Critical For the Pancreatic Developmentmentioning
confidence: 99%